1995
DOI: 10.1002/jab.770060104
|View full text |Cite
|
Sign up to set email alerts
|

Fretting corrosion accelerates crevice corrosion of modular hip tapers

Abstract: The use of multiple-component systems in orthopedic surgery gives the surgeon increased flexibility in choosing the optimal implant, but introduces the possibility of interfacial corrosion. Such corrosion could limit the longevity of prostheses due either to tissue reactions to corrosion products, or to device failure. The incidence and nature of corrosion of modular total hips was evaluated in a consecutive series of 79 retrieved implants from University Hospitals of Cleveland. Surfaces were examined with ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
120
1
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(124 citation statements)
references
References 20 publications
0
120
1
3
Order By: Relevance
“…Increases in serum levels of cobalt were previously observed in the setting of metal-on-metal articulations and failed implants with modular head-neck junction corrosion and poorly functioning primary total hip prostheses 24,25 . Factors that could affect the fretting corrosion process, causing increased cobalt concentrations, include taper size of the femoral stem, geometry, tolerances, assembly forces, surface finish, and metallurgy 22,26,27 . In the current study, there were no significant differences in cobalt levels between the CoCr group, in which extensively porous-coated cobalt-alloy femoral stems had been used, and the titanium group, in which proximally porous-coated titanium-alloy femoral stems had been used, despite the fact that there were significant elevations at all follow-up intervals in comparison with the levels seen in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in serum levels of cobalt were previously observed in the setting of metal-on-metal articulations and failed implants with modular head-neck junction corrosion and poorly functioning primary total hip prostheses 24,25 . Factors that could affect the fretting corrosion process, causing increased cobalt concentrations, include taper size of the femoral stem, geometry, tolerances, assembly forces, surface finish, and metallurgy 22,26,27 . In the current study, there were no significant differences in cobalt levels between the CoCr group, in which extensively porous-coated cobalt-alloy femoral stems had been used, and the titanium group, in which proximally porous-coated titanium-alloy femoral stems had been used, despite the fact that there were significant elevations at all follow-up intervals in comparison with the levels seen in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Large-diameter femoral heads and trunnion geometry were common features identified in the studies that associated elements of implant design with tribocorrosion in taper junctions [7,18,19,32]. Larger head sizes increase torsional forces at the trunnion [9], and this may be a contributing factor in the increased failure rates seen metalon-metal (MoM) THAs [17,22], which have a high revision rate of 19% after 12 years [2].…”
Section: What Clinical Problems Have Been Reported In Patients With Mmentioning
confidence: 99%
“…In vitro and finite element studies have shown that fretting would occur from micromotion at the interface [14,15,22,25]. Retrieval studies have documented corrosion of the headneck interface secondary to fretting [5,16,18,23]. Such corrosion can be potentiated by crevice corrosion, or that which occurs in spaces to which access of the working fluid from the environment is limited [5-8, 12, 14, 16, 18, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Increased offset reportedly causes higher degrees of corrosion. In a retrieval study, Brown et al [5] reported that +5 and +10 mm neck extensions have higher degrees of corrosion than necks without an extension. They noted the highest corrosion occurred in the distal inferior (closer to stem neck interface) and proximal superior aspects of the femoral neck.…”
Section: Discussionmentioning
confidence: 99%